Phytochemical and biological activity study of Calophyllum canum - Alkhamaiseh, Suhaib Ibrahim; Bakhtiar, M. Taher; Ahmad , Farediah (2010)
Calophyllum canum or (Bintangor Batu) is a Malaysian plant which belongs to the family of Guttiferae. This family considered being a source of xanthons and flavonoids, which has shown lately the biological activity against bacterial, fungus and cancer cells. The most well known species Calophyllum Ianigerum which found in Sarawak shown a biological activity against human immunodeficiency virus (HIV). During the last three decades, the studies have been done for isolating these certain compounds. In this research we are concentrating on phytochemical study of C.canum. The stem bark of this plant dried and grinded to get a powder form, and then it has been extracted by using Soxhlet extraction method, where the extraction started with Hexane, Ethyl acetate and Methanol. The extracts were isolated by using Chromatography method (vacuum and column), the hexane and ethyl acetate fraction yield six pure compounds marker as (cc1-cc6). The crude extract examined against bacterial gram (positive and negative), by using the disk diffusion method. Also it has been tested to observe any antioxidant behaviors. As well as the crude and identified compounds will be tested for there anticancer activity against lung, leukemia, colon, breast and cervix cancer. The cell growth will be monitored by inhibition of cell proliferation with MTT assay. For the identification, we used the spectroscopic techniques (NMR, IR, MS, and UV/Vis) for interpretation the structure of these pure compounds. The results are under processing to draw the structure.